Tourists' Perceptions of Religious Tourism Experience at the Tomb of Sunan Ampel Surabaya - Prabowo, Oxy Hendro (Politeknik Siber Cerdika Internasional, 2025)
This study aims to examine tourists' perceptions of the religious tourism experience at the tomb of Sunan Ampel, Surabaya, which is one of the most important religious tourism destinations in Indonesia. This research uses a qualitative approach with a descriptive method to describe in depth the experiences of tourists visiting the tomb. Data were collected through in-depth interviews with tomb managers, questionnaires distributed to licensed employees, and direct observation at the site. The results showed that the majority of tourists were satisfied with the spiritual aspects they experienced, but many complained about the limited facilities, such as inadequate seating and narrow worship space. In addition, the lack of clear historical information is also one of the factors that reduce the quality of the tourist experience. The implication of this study is the need to improve facilities, develop training programs for staff, and provide more educative information for visitors. This research is expected to provide input for the manager of Sunan Ampel tomb in improving the quality of service and management of religious tourism in Indonesia.